Deciphering Digital Hate: Assessing the Evidence between Online Speech and Offline Violence in Africa (Global Media Journal - German Edition, 2024)
From Ethiopia to Sudan, there has been significant concern about the role of hate speech and incitement on social media to promote offline violence and, at its most extreme, genocide. These questions have become more urgent with the growth of large language models and Artificial Intelligence that are increasingly shaping online speech and may amplify existing concerns. In this paper, we interrogate the assumptions and myths about the causal link between online speech and its impact on the offline world by evaluating the empirical evidence. Overall, we found that there is limited evidence pointing to this direct association and, in line with broader literature on the underlying causes of violence, our review points to longer-term contextual, historical, and economic factors that often drive conflict, particularly in Africa. We conclude by identifying major evidence gaps and highlighting the need for caution when attributing the impact of online hate speech on violence.
Keywords: Online Speech; Violence; Hate Speech; Content Moderation; Africa; Social Media; Conflict